Early Mini-Invasive Treatment of Persistent Cervical Dysplasia: Clinical Outcome and Psycho-Relational Impact - Plotti, Francesco; Rossini, Gianmarco; Ficarola, Fernando; De Cicco Nardone, Carlo; Montera, Roberto; Guzzo, Federica; Luvero, Daniela; Fabris, Silvia; Angioli, Roberto; Terranova, Corrado (Frontiers in Surgery, 2022)
Introduction After the diagnosis of L-SIL, 77. 3% had a persistent infection and anomalous Pap Test results. Many of these patients had highlighted psychological consequences such as anxiety, hypochondria, fear of cancer, and sexual problems. Several studies suggested that the clearance of HR-HPV infection could be accelerated by cervical excisional procedures, especially in L-SIL. In consideration of the psychological implications for HPV infection and related dysplasia in patients with CIN1 at PAP-smear and HR-HPV positivity at least for 6 months, we decided to plan a prospective study where we tried to anticipate excisional cervical using a minimally invasive treatment: thin loop electrosurgical excision procedure (t-LEEP). This study aims to analyze the clearance of HR-HPV after 6 and 12 months, clinical outcomes related to t-LEEP, and the psycho-relational impact at 12 months after t-LEEP. Materials and Methods We enrolled patients with the diagnosis of L-SIL at PAP-smear and HR-HPV positivity with a persistent CIN 1 (at least for 6 months), confirmed by cervical biopsy. All enrolled patients underwent t-LEEP. We followed prospectively and performed for all patients the HPV DNA test at 6 (T1) and 12 months (T2) and STAI-Y and FSFI scores at T0 and T2. Results We prospectively enrolled 158 patients, 22 are excluded for the established criteria. Patients with HR-HPV and CIN 1 lesions treated with t-LEEP had an overall clearance of 83.8% at T2. In subgroups analysis at T2, we had a regression: in smoker 71.8%, in contraceptive users 69.5%, in patients aged <25 years 100%, aged 25–30 years 85%, aged 30–35 years 94.4%, aged 35–40 years 92%, and aged ≥40 years 89.1%, in HPV-16 96.4%, in HPV-53 89.5%, in HPV-18 87.5%, in HPV-31 86.6%, and in coinfected 3.5%. STAI-Y and FSFI after t-LEEP (T2) were statistically significant, reducing anxiety status and improving sexual function. Conclusion Based on these results, the use of t-LEEP in patients with persistent CIN 1 and HPV-HR at least for 6 months could be useful for accelerating HPV-HR clearance, in particular, for a subpopulation patient with an increased risk of progression and/or patients with psychological and sexual consequences of carrying an HR-HPV infection.